Ukiran Ornamen Tradisional Minangkabau pada Dekorasi Pelaminan - Nofrial Nofrial; Purwo Prihatin; Marten Agung Laksono (Corak : Jurnal Seni Kriya, 2021)
The traditional Minangkabau ornament that has applied to Rumah Gadang currently has experienced product diversification. One of the developments is for the carving of the wedding aisle decoration. This study aims to document the types of motifs, analyzes their development concepts, engraving techniques, and functions of traditional Minangkabau ornaments in the wedding aisle decorations, in Pariaman and Padangpanjang. The method of this study consists of qualitative methods and analytic descriptive analysis with cultural, sociological, and aesthetic approaches. The well-known traditional Minangkabau ornaments in the wedding decorations for instance are Kaluak Paku motifs, Itiak Pulang Patang, Aka Cino Sagagang, Saik Ajik, Pucuak Rabuang and Siriah Gadang. Generally, these ornaments have transformed in shape to adapt the placement media purpose, the practicality of engraving, and its aesthetics. Ornaments are made on spongy rubber media with cutting techniques. The functions of ornaments are to decorate and as an identity of Minangkabau wedding tradition aisle. Ornamen tradisional Minangkabau yang diterapkan pada Rumah Gadang, saat ini telah mengalami diversifikasi produk. Salah satu pengembangannya untuk ukiran dekorasi pelaminan. Penelitian ini mendokumentasikan jenis motif, menganalisis konsep pengembangannya, teknik pembuatan dan fungsi ornamen tradisional Minangkabau pada dekorasi pelaminan, di Pariaman dan Padangpanjang. Melalui metode kualitatif, analisis deskriptif analitik dengan pendekatan budaya, sosiologis dan estetik. Diketahui ornamen tradisional Minangkabau pada dekorasi pelaminan terdiri dari motif Kaluak paku, Itiak pulang patang, Aka cino sagagang, Saik ajik, Pucuak rabuang, and Siriah gadang. Secara umum ornamen tersebut telah mengalami perubahan bentuk, guna penyesuaian media penempatan, kepraktisan pembuatan dan estetikanya. Ornamen dibuat pada media karet spon, teknik sayat dan toreh. Fungsi ornamen untuk penghias dan pemberi ciri khas pelaminan adat Minang.